Bank Syariah Indonesia's Strategy in Maintaining the Loyalty of Priority Customers at CV Fawas Jaya - Ritonga, Aprilia Amanda; Yanti, Nursantri; Inayah, Nurul (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2025)
This study aims to explore the strategies implemented by Bank Syariah Indonesia (BSI) in maintaining the loyalty of its priority corporate customers, focusing on a case study of CV. Fawas Jaya as one of BSI’s key business clients. The research is grounded in the significance of retaining high-value clients, particularly in the Islamic banking sector, which emphasizes justice, trust, and value-based service. This study employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews, observations, and documentation involving both BSI and CV. Fawas Jaya. The findings reveal that BSI employs several service strategies including the provision of dedicated relationship managers (RMs), ease of access to exclusive services, tailored Sharia-compliant financial products, and proactive communication aimed at building long-term partnerships. The main factors influencing CV. Fawas Jaya’s loyalty include trust in Sharia principles, satisfaction with services, and strong interpersonal communication. Despite facing challenges such as limited human resources and occasional technical issues, BSI continues to innovate to improve service effectiveness. This study concludes that BSI’s strategic efforts have been generally effective in maintaining the loyalty of its priority corporate clients.